Assessment of timely detection of abdominal aortic aneurysm in Serbian population based on the data from SERBVASC registry of operated patients - Pešić, Slobodan; Tanasković, Slobodan; Stepanović, Nemanja; Joković, Vuk; Tomić, Aleksandar; Babić, Srđan; Roganović, Andrija; Popović, Miroslava; Končar, Igor (Medical Research, 2023)
Introduction Screening of males older than 65 years old for abdominal aortic aneurysm (AAA) has been proved effective in some countries. Incidence of AAA in Serbian population has not been described since. Aim of the study was to assess number of elective and urgently operated patients with AAA and to estimate incidence according to the population. Methods Data were obtained from Vascular surgery registry - Serbvasc wich is created by 16 institutions. Data about demografic caracteristics were obtained from publication of Statistical office of the Republic of Serbia. For statistical analysis descriptive statistics methods were used and values are expressed per 100 000 inhabitants.Results During the year 2021, 422 operations were performed in 7 hospitals due to asymptomatic, symptomatic and ruptured AAA in 323 (76,54%), 37(8,76%) and 62 (14,69%) patients pespectively. Incidence of electively operated AAA is 8,06 cases per 100 000 inhabitants, incidence for operated ruptured AAA is 1,55 cases per 100 000 inhabitants. Overall incidence of all operatively treated AAA is 10,53 cases per 100 000 inhabitants. Incidence of AAA treated in population older than 65 years is 42,40 per 100.000 inhabitants older than 65 years.Conclusion Incidence of operatively treated elective AAA is lower than those found in literature while rate ruptured AAA is more than twofold higher than published in the recent literature.The most efficient strategy for reduction of urgently treated AAA is implementation of screening for AAA in groups with higher risk.
Keywords: Abdominal aortic aneurysm; registry; hospital incidence